TUGU RASAH (TUILES SORGHUM BERAS MERAH) SEBAGAI CAMILAN SEHAT FUNGSIONAL - Kokom Komariah, Intan Purnama Tiara Fitri (Prosiding Pendidikan Teknik Boga Busana, 2020)
The high consumption of wheat flour in Indonesia can be reduced by substituting sorghum flour and red rice flour. In this study sorghum flour and red-rice flour were used as ingredients for making healthy snacks, namely Tugu Rasah (Tuiles Sorghum Beras Merah). The purpose of this study was to obtain a substitution formula for sorghum flour and red rice flour, knowing the community's acceptability and nutritional value of Tugu Rasah (Tuiles Sorghum Beras Merah) product. This study used research and development (R & D) with 4D models (Define, Design, Develop, Disseminate). Data analysis was carried out descriptively. The research panelists consisted of 30 trained panelists and 30 untrained panelists 80 people. Based on the research results, the formula used was 75% sorghum flour and 25% red-rice flour. In the research of Tugu Rasah (Tuiles Sorghum Beras Merah) with substitution of sorghum flour and red-rice flour as a functional healthy snack can be accepted by the general public. This is based on the results of the T Test which has been done by looking at the average yield of each product characteristic (color, aroma, texture, taste, overall). Based on the proximate test that has been done, the highest content was found in carbohydrates with the amount of 58.23 gr and the smallest was the ash content with the amount of 2.8 gr. In addition, the energy content of Tugu Rasah (Tuiles Soghum Beras Merah) was 420.57 cal / 100gr.